Auditor underreporting of time and moral reasoning: An experimental lab study* - PONEMON, LAWRENCE A. (Contemporary Accounting Research, 1992)
Abstract. This paper introduces the theory of moral reasoning as a valid determinant of the underreporting of audit time. In an experimental lab design for a sample of 88 auditors from a national public accounting firm, actual underreporting on an audit task was observed. Findings show that underreporting is systematically related to the auditor's level of moral reasoning as measured by the Defining Issues Test (DIT). Here those with relatively low DIT scores were shown to underreport most severely. Results also show that although an unattainable time budget affects behavior, peer pressure has the most significant impact on underreporting. The present study makes three important contributions to the auditing and psychology literature. First, it establishes the significance of peer pressure as an antecedent to underreporting. Second, it shows that an auditor's moral reasoning explains actual underreporting behavior under conditions of work‐related pressure. Third, it reveals marked underreporting under simulated audit conditions.